Island Arc Signatures from the Waziristan Igneous Complex NWFP Pakistan - Ahmad, Waseem; Hamidullah, S. (Journal of Himalayan Earth Sciences, 1987)
The Waziristan igneous complex consists of peridotite, gabbro, diorite, diabase and a variety of volcanic rocks. Petrographic studies and mineral chemistry of the rocks contradict their oceanic crust origin and evince an island arc parentage. The high Mg# (89-95) of the olivine and pyroxenes, and absence of plagiocalse in the cumulus peridotite suggest crystallization at high pressures - not typical of oceanic crust. The calcic-plagioclase (An90-97) and clinopyroxene (Wo44-46En44-50F5-l2) association in the gabbroic rocks of the Waziristan igneous complex is akin to other island arc-related gabbros. A variety of diagrams used for discrimination ofclinopyroxenes from different tectonic environments, also indicate the island arc affinity of this complex.